Clinical Pharmacology Characterization and Dose Selection of Xaluritamig, a Next Generation XmAb® 2+1 T-Cell Engager, in Prostate Cancer Patients - Kuipers-Connarn, Jamie N; Pourzanjani, Arya; Bose, Maitreyee; Modi, Saurabh; Stieglmaier, Julia; Murphy, Alexis; Mehta, Khamir; Upreti, Vijay V (Journal of clinical pharmacology, 2025)
Bispecific T-cell engagers have revolutionized the treatment and management of hematological malignancies and more recently have started making similar strides for solid tumor indications, with opportunities to become best-in- class therapeutics for cancer. Xaluritamig is a novel bivalent XmAb® 2+1 T cell engager with two STEAP1 binding sites and one CD3 binding site being developed for solid tumors with the primary indication of metastatic castrate resistant prostate cancer (mCRPC). The First-In-Human (FIH) study showed promising anti-tumor activity in mCRPC patients, and the program is currently in late phase clinical development. Xaluritamig was administered as an intravenous infusion once weekly (QW) or once every other week (Q2W) in the dose escalation of the FIH study at dose levels ranging from 0.001 to 2 mg. Initial pharmacokinetic (PK) characterization of xaluritamig exhibited approximately dose-proportional increase in exposures over the dose levels explored, with an estimated terminal half-life of ≈9 days, assuming subjects had no anti-drug antibodies, calculated via the population PK model. The time at which maximum concentration (C ) occurred was typically at the end of infusion (median ≈ 1 h), as expected with IV administration. Additionally, thorough dose-exposure-response analyses integrated observed data and model-based simulations of PK, key efficacy endpoints, and safety events to support the evaluation of the target doses 0.75 mg QW, 1.5 mg QW, and 1.5 mg Q2W in dose expansion. This work provides the framework for which modeling and simulations can be used to guide dose selection for dose expansion at an early stage of development adhering to the recent principles of Project Optimus.